Sindrom Stevens-Johnson yang Disebabkan oleh Carbamazepine pada Pasien Epilepsi: Laporan Kasus: Laporan Kasus - Harlim, Charity; Kelvin, Kelvin; Hartati, Agung Triana (PT Kalbe Farma Tbk., 2026)
Introduction: As a first-line antiepileptic drug for partial and tonic-clonic seizures, carbamazepine requires long-term use. This drug carries a risk of Stevens-Johnson syndrome (SJS) or toxic epidermal necrolysis (TEN) reaction. Case: A 23-year-old woman with a history of seizures had reddish rashes on the face, neck, chest, back, and left and right upper extremities covering 10% of the body surface area (BSA) after taking carbamazepine 200 mg twice a day for her seizures. Discussion: The patient was given methylprednisolone 16 mg tablets twicea day, IV diphenhydramine twice a day, and other symptomatic drugs. After 9 days, the patient was discharged with phenytoin 100 mg tablets twice a day as a substitute for carbamazepine. Early treatment with high-dose systemic steroids provides benefits of rapid recovery,especially in SJS patients where skin damage is not too extensive and can be restored by the anti-inflammatory effects of steroids. The main treatment of SJS/TEN is early recognition and immediate discontinuation of the drug. Conclusion: Carbamazepine is often a risk factor forSJS, thus an alternative treatment is needed.